Designating a portion of the Arctic National Wildlife Refuge as part of the national wilderness preservation system : hearing before the Subcommittee on Environmental Protection of the Committee on Environment and Public Works, United States Senate, One Hundred Second Congress, first session, on S. 39 . April 19, 1991. - United States. Congress. Senate. Committee on Environment and Public Works. Subcommittee on Environmental Protection. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., Congressional Sales Office, U.S. G.P.O., 1991)
Shipping list no.: 91-520-P. Distributed to some depository libraries in microfiche. Includes bibliographical references (p. 53-79). Mode of access: Internet.